Ginkgo biloba Extract Prescriptions Are Associated with Slower Progression of Dementia Severity—Analysis of Longitudinal Real-World Data - Jens Bohlken; André Hajek; Martin Burkart; Karel Kostev (Brain Sciences)
Background/Objectives: Previous research indicates that Ginkgo biloba extract (Gbe) may contribute to slowing down the progression of dementia. This retrospective cohort study analyzed the association between Gbe prescriptions and the progression of dementia severity in a real-world setting. Methods: This study was conducted using data from patients with an initial diagnosis of mild or moderate dementia between January 2005 and December 2022 from the IQVIA™ Disease Analyzer database. The follow-up period was up to 10 years. The association between Gbe prescription and dementia severity progression was assessed by Kaplan–Meier analysis and Cox regression, with adjustments made for age, sex, health insurance status, physician specialty, co-prescription of antidementia drugs, and co-diagnoses. Results: A total of 4765 patients were included, of whom 177 were prescribed Gbe. The cumulative incidence of dementia severity progression was 12.7% for patients with Gbe prescription and 22.1% for those without. Gbe prescription was associated with a significantly decreased risk of dementia severity progression (hazard ratio: 0.50; 95% CI: 0.27–0.95), both in patients with mild (HR: 0.44; 95% CI: 0.22–0.90) and moderate dementia (HR: 0.24; 95% CI: 0.06–0.98). Conclusions: This study provides evidence that Gbe prescription is associated with a reduced risk of dementia severity progression in a real-world setting.